Physical Layer Security in N-Pair NOMA-PLNC Wireless Networks - Rajkumar, Samikkannu; Jayakody, Dushantha Nalin K.; Alkanhel, Reem; Muthanna, Ammar (IEEE access, 2022)
In this paper, the effective end-to-end secure communication of N-pair cellular network is studied. Promising multiple access scheme known as non-orthogonal multiple access (NOMA) and physical layer network coding (PLNC) scheme are employed to improve the spectral and the temporal efficiency respectively. Also, this proposed model uses the physical layer security to ensure the secure wireless communication. It is assumed that the eavesdropper (Eve) tries to trace the confidential message from the legitimate user's. Hence, they generates the artificial noise (AN) to confuse the Eve. Closed form expression for the end-to-end outage probability of the proposed N-pair NOMA-PLNC wireless network is derived. Further, a closed form expression for the secrecy outage probability of the proposed network is derived using homogeneous Poisson point process (HPPP) and Gaussian -Laguerre quadrature. Numerical results are presented to validate theoretical findings. It is noteworthy that uplink performance of the proposed network is better than the network without PLNC scheme.